PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPS SEKOLAH DASAR - Gading, I Ketut; Dian Kharisma, Kadek (Universitas Pendidikan Ganesha, 2017)
This research aims to know the differences of social science learning outcomes between groups of students who got the treatment model of learning Make A Match-assisted audio visual with a group of students who did not receive treatment with a model of learning Make A Match-assisted audio visual. This research includes research of artificial experiments that use of non-equivalent design posttest only control group design. As many as 32 students SDN 3 Pacung entangled as a group of experiments and 32 students SDN 1 Pacung entangled as the control group. Experimental treatment given to groups of models of cooperative learning types make a match for a month as much as 8 times. While the control group dibelajarkan with learning that naturally occurs in the treatment group of experiments underway. Student learning outcomes data collected through methods of tests with a test instrument shaped as a multiple choice question. Collected data were analyzed by descriptive statistics and statistical infirensial test-t. The results of this study found that there is a difference between the social science study results of students who got the treatment model of learning Make A Match of audio visual and assisted the Group of students who did not receive the treatment model of learning Make A Match-assisted audio visual on IPS subjects class IV. This is demonstrated by the results of significant value < 0.05 then H1 accepted and H0 is rejected and an average score of experimental group students i.e. 23.28 and score an average control group i.e 15.00. This means experimental > control, so that it can be concluded the implementation of cooperative learning model types Make A Match using the media audio visual effect on the results of studying social science at grade IV.